Understanding Bai' Bithaman Ajil financing: A study of northern region Agrobank employees in Malaysia - Murugiah, Logasvathi; Che Jaafar, Dzulfadly (2015)
The purpose of this study is to assess the understanding of Bai’ Bithaman Ajil (BBA) financing contract between Agrobank employees attached at branches and business center (regional office) in the northern states of Peninsular Malaysia namely Penang, Kedah and Perlis. The research presents primary data collected by self-administered questionnaires involving a sample of 40 respondents who represents executives from the lower - management group with direct involvement in commercial financing-related functions.A multiple regression analysis had been employed in this study.The finding shows that knowledge and commitment are the two significant factors which could affect employees’ understanding of BBA financing contract. The empirical evidence of this study highlights the importance of Agrobank to groom a knowledgeable workforce with true commitment in Islamic banking aspects in order to ensure its transformation process would chart another remarkable milestone in spurring the growth of Islamic banking industry in Malaysia.